2001
DOI: 10.1002/chir.10007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of beta radiation on the crystallization of sodium chlorate from water: A new type of asymmetric synthesis

Abstract: Sodium chlorate is an achiral molecule that crystallizes from water in the chiral space group P2(1)3. In the absence of chiral perturbations, a random distribution of (+) and (-) crystals is obtained. Kondepudi(2) has shown that constantly stirring an evaporating NaClO(3) solution gives mostly either (+) or (-) crystals. Repeating this experiment many times gives equal numbers of (+) and (-) sets of crystals. Herein we report that when evaporating aqueous NaClO(3) is subjected to beta particles from an Sr-90 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 26 publications
2
51
0
Order By: Relevance
“…Experimental findings that BioDisc-3 may alter the structure of water cannot fully explain chiral symmetry breaking in this study. This is consistent with earlier research demonstrating that certain external treatments, beta and positron radiation, lead to chiral symmetry breaking for this crystal system (Mahurin et al, 2001). In addition, a direct current electric field stimulation (3.5 -17.5 V/cm) of the aqueous solution was also shown to yield more dcrystals (Chen and Chen, 2006).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Experimental findings that BioDisc-3 may alter the structure of water cannot fully explain chiral symmetry breaking in this study. This is consistent with earlier research demonstrating that certain external treatments, beta and positron radiation, lead to chiral symmetry breaking for this crystal system (Mahurin et al, 2001). In addition, a direct current electric field stimulation (3.5 -17.5 V/cm) of the aqueous solution was also shown to yield more dcrystals (Chen and Chen, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…2002). Solutions exposed to beta particles, which are spinpolarized, from radioactive 38 Sr 90 , yielded predominantly d-crystals (Mahurin et al, 2001). NaClO3 crystallizations exposed to positrons, which are spin-polarized in a direction opposite that of beta particles, from radioactive Is there an effect of various subtle external stimuli, some of which purportedly affect water structure, on chiral symmetry breaking during sodium chlorate crystallization?…”
Section: Introductionmentioning
confidence: 99%
“…An excellent summary of that work from the University of Michigan can also be found in Rich [7]. A somewhat more recent relevant study, on the effect of β radiation on the crystallization of sodium chlorate from water, by Mahurin et al [8] concluded that the polarization of the electrons (in this case) was correlated with the chirality of the crystals being generated. Finally, for completeness, we also note that early work on the origins of biological chirality was also conducted with energetic β particles rather than slow β particles.…”
Section: Introductionmentioning
confidence: 97%
“…Both NaClO 3 and NaBrO 3 are cubic with space group P2 1 3. The convenient determination of crystal chirality without orientation makes NaClO 3 an ideal material for the investigation of crystal chiral symmetry breaking ͑Kondepudi et al., 1990;Mahurin et al, 2001;Chen and Chen, 2007;Song et al, 2008͒. There are a number of studies on the investigations of the mechanism of chiral symmetry breaking of NaClO 3 crystals ͑Kondepudi et al., 1990;Martin et al, 1996;Cartwright et al, 2004;Viedma, 2004;Viedma, 2005͒. However, studies of the chirality of NaCl 1−x Br x O 3 mixed crystals are few.…”
Section: Introductionmentioning
confidence: 99%